Photochemical internalization and gemcitabine combined with first-line chemotherapy in perihilar cholangiocarcinoma: observations in three patients - Dechêne, Alexander; Kasper, Stefan; Olivecrona, Hans; Schirra, Joerg; Trojan, Joerg (Endoscopy International Open, 2020)
Photochemical internalization (PCI) is a technology to induce a localized, intracellular enhancement of therapeutics that are processed through endosomal pathways, including gemcitabine in malignant cells. In addition to a direct phototoxic and tumoricidal effect, PCI specifically disrupts endosomal membranes and, thereby, the compartmentalization of certain cytotoxic compounds to enhance a drug’s intended intracellular target reach within the tissue treated.Non-resectable extrahepatic cholangiocarcinoma (eCCA) is a common primary tumor and gemcitabine/cisplatin chemotherapy is widely considered standard of care for it. PCI is well suited as an endoscopic intervention, and clinical observations in three subjects participating in a phase I/IIa dose escalation safety trial are described. The trial included patients with perihilar, non-resectable CCA suitable for standard-of-care chemotherapy. Per protocol, a single endoscopic PCI procedure with gemcitabine was conducted at the initiation of standard gemcitabine/cisplatin therapy. Sixteen patients enrolled in the initial dose escalation phase of the trial, which later was extended to explore the safety of a second PCI procedure during chemotherapy.While limited to a case series, the various clinical observations described here serve to illustrate the effects of localized, perihilar tumor targeting in appropriate patients by any safe methodology, including PCI. As previously indicated by clinical data using other localized treatment modalities, adding a directed, tumor-targeting treatment to systemic therapy to ameliorate the progressively expanding extrahepatic tumor burden can have important effects on the overall outcome of systemic treatment in many patients who have incurable eCCA.